Revealing the wetting mechanism of Li+-doped ionic liquids on the TiO2 surface. (16th January 2023) - Wang, Chenlu; Liu, Guangyong; Cao, Renqiang; Xia, Yu; Wang, Yanlei; Nie, Yi; Yang, Chao; He, Hongyan
Highlights: The ion exchange process between Li + and P13 + at the interface was clarified. Hydrophilic-to-hydrophobic transition occurs as the Li + content rises from 0 to 80 %. Regulating mechanism of the dynamical wetting behavior of Li + -doped IL was revealed. Abstract: The sensible design of ionic liquid (IL)-based application relies on a thorough knowledge of the structure and characteristics of electrolyte–electrode interfaces. Here, the wetting processes of the Li + -doped ILs droplets on the TiO2 -B(1 0 0) surface are investigated by molecular dynamics simulation. According to the spatial distributions of components, doped Li + prefers to substitute the ILs and adsorb to the substrate, causing the orientation changes of the ILs, weakening the ILs-substrate interaction, and slowing down the wetting process significantly. As Li + concentration rises from 0 to 80 %, the contact angle increases from 86.97 to 131.18°, inducing the hydrophilic-to-hydrophobic transition. On the contrary, heating up would reduce the contact angle by extending the contact length and enhancing the maximum density of Li + -doped ILs at the interface. These quantitative results prove that the dense adjacent layer in the interface induced by the strong adsorption of Li + dominates the wetting process of Li + -doped ILs.